2017
DOI: 10.1093/rpd/ncx292
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Radiation Therapy Technologist Received Dose From Induced Activation in High-Energy Medical Linear Accelerators

Abstract: Despite all advantages for using high-energy photons for radiotherapy, high-energy photon beams (≥10 MV) induce photonuclear and neutron capture interactions, which result in producing radionuclide byproducts inside the Linac head and bunker, exposing radiation therapy technologists (RTTs) and patients to excessive dose. By the use of higher photon energy, greater number of monitor unit, greater field size and adding treatment accessories, induced dose rate become greater in the isocenter mainly due to activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
1
4
1
Order By: Relevance
“…This difference between open and closed fields was found to be more than 100 times, contrary to other studies, which reported up to a 7-fold increase in neutron dose equivalent or neutron fluence by increasing the field size. [2][3][4] Furthermore, it is well-known that the energy threshold for photodisintegration interactions for all elements in the treatment room exceeds 6 MV, which also was confirmed by Carlone and colleagues in the publication. Therefore, when operating in 6 MV photon mode, measurements of neutron dose with either open or closed jaws are unlikely to differ significantly since both are in close proximity to zero.…”
supporting
confidence: 54%
“…This difference between open and closed fields was found to be more than 100 times, contrary to other studies, which reported up to a 7-fold increase in neutron dose equivalent or neutron fluence by increasing the field size. [2][3][4] Furthermore, it is well-known that the energy threshold for photodisintegration interactions for all elements in the treatment room exceeds 6 MV, which also was confirmed by Carlone and colleagues in the publication. Therefore, when operating in 6 MV photon mode, measurements of neutron dose with either open or closed jaws are unlikely to differ significantly since both are in close proximity to zero.…”
supporting
confidence: 54%
“…The induced activity has attracted considerable attention in the high-energy radiotherapy. [9][10][11] The induced radioisotopes are the primary occupational radiation source to therapists. The primary physical mechanism of the induced activity is the photonuclear reaction (γ, n) for photon with energy higher than 8 MeV, [12][13][14] followed by the photoneutron moderation and capture reactions (n, γ) in the linac head, bunker, air, and patient body.…”
Section: Introductionmentioning
confidence: 99%
“…), and operation details (treatment room entry time, workload, etc.). 9,10 Therefore, when the new linac and fractionation are applied, studying the induced activity is necessary and important. In this study, the induced activity in 10 FFF SBRT was investigated by γ spectroscopy and dosimetry measurements, and the annual induced dose to therapists was evaluated on the basis of one mathematical model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoneutrons are produced as a result of interaction of high energy photons with materials in the radiotherapy linear accelerator head including W, Pb, Cu and Fe. In particular, the high atomic number materials in the linac head: tungsten and lead have very low absorption cross sections for the photoneutrons produced and thus does not affect the intensity of the produced photoneutrons [5]. Photoneutrons produced in medical linear accelerator could undergo (n,γ) neutron capture reaction inducing different activation products.…”
Section: Introductionmentioning
confidence: 99%